SYSTEMATIC LITERATURE REVIEW : PEMANFAATAN LIMBAH KULIT BUAH-BUAHAN SEBAGAI ADSORBEN SERTA KAITANNYA DENGAN INTEGRASI KEISLAMAN - Judha Syah Putra; Andi Mulsidah; Rezi Amalia Putri; Fitri Refelita (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
AbstractGrowth and development in the industrial sector has made residents contribute to the waste that enters the environment. Imperfect waste treatment causes pollution to the environment and waters, so the water quality has decreased. The decline in water quality is caused by water pollution where foreign substances enter and leave. One of them is heavy metal. A number of studies have been carried out to treat and remove heavy metal ions in waters, one of which is the adsorption process. The adsorption method usually utilizes waste that is often disposed of and even modifications or activations are carried out in order to expand the surface area of the absorbent material. This review article discusses the adsorption method by utilizing Indonesian typical fruit peel waste for the last 10 years. From several studies collected, it was found that waste from typical Indonesian fruit peels was effective in absorbing heavy metal waste. Fruit peel waste that has high effectiveness is lemon peel waste with an absorption capacity of 98.4% on Cd metal, with an pH 8 and optimum contact time of 2 hours. This review can be an alternative for the manufacture of other absorbent materials and eliminate metal pollution in the aquatic environment.Keywords : Water pollution, Heavy Metals, Adsorption, Indonesian Fruit Peel Waste